Perinatal feline immunodeficiency virus infection: a model of in utero and milk-borne HIV-1 transmission - Allison, Robin Walsh, author; Hoover, Edward A., advisor; Blair, Carol D., committee member; Olver, Christine S., committee member; Avery, Anne, committee member (Colorado State University. Libraries, 2002)
Mother-to-child transmission of human immunodeficiency virus type-1 (HIV) occurs in utero, during delivery, and postnatally by breastfeeding. Milk-borne virus may be responsible for up to two-thirds of overall vertical transmission, and yet little is known about the role of cell-free and cell-associated virus in milk, and no studies have identified cellular sources of HIV in mammary gland. Most children of HIV-infected women are not detectably HIV-positive, although many have HIV-specific immune responses that suggest viral exposure. We studied mother-to-offspring transmission of feline immunodeficiency virus (FIV), the feline equivalent of HIV infection, and documented extensive viral shedding in milk, identified FIV-infected cells in mammary gland, and uncovered atypical 'covert' FIV vertical transmission. These results have relevance for the design of effective intervention strategies to reduce perinatal HIV transmission. Kittens born to FIV-infected cats were assayed for virus in blood and/or tissues. DNA polymerase chain reaction (PCR) detected pro virus in blood of all kittens on the day of birth, indicating in utero FIV infection. FIV antibody levels declined and became undetectable past 4 months of age, consistent with maternal antibody. No CD4 or CD8 T-cell abnormalities were observed, and kittens remained clinically healthy for over one year. Provirus was detected more easily in tissues than in blood, suggesting sequestration of virus with downregulated replication. This occult FIV vertical transmission may be a good model to investigate in utero viral exposure and potential protection from subsequent viral challenge. Milk and blood samples were collected from FIV-infected cats. Viral RNA loads in early milk were as much as 4 log-fold higher than those in plasma, whereas proviral loads in milk cells were consistently lower than those in blood; thus virus appears to be concentrated in early milk. Proviral loads were equivalent in separated blood cells enriched for mononuclear cells versus polymorphonuclear cells, suggesting FIV infection of neutrophils. Additionally, treatment of cats during pregnancy with the antiretroviral drug PMPA was associated with decreased kitten birth weight and viability. Cellular sources of FIV were sought in mammary gland biopsies from FIV-infected cats. In situ hybridization (ISH) revealed numerous FIV-infected cells in primarily intraepithelial locations. Combined immunohistochemistry and ISH identified the majority of these cells as CD3+ T-cells. Significantly more T-cells were observed in mammary glands of FIV-infected versus naive cats. These results suggest a reservoir of FIV-infected cells in mammary gland that may promote viral dissemination in milk.
Keywords: pathology; immunology